Acute Ischemic Stroke in Patients With Pulmonary Arteriovenous Malformations: Paradoxical Embolism or Epiphenomenon? - Ankita Das; Jacob D. Greisman; Sima Vazquez; Eric Feldstein; Eris Spirollari; Aiden Lui; Katie Yang; Jose F. Dominguez; Oleg Epelbaum; Kassem Harris; Neisha Patel; Ji Chong; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background Pulmonary arteriovenous malformations (PAVM) are pathological connections between arterial and venous circulations in the lung. The anomalous channel provides a conduit for emboli of venous origin to migrate paradoxically. With access to systemic circulation, thromboembolic processes such as deep vein thrombosis may increase the risk of cerebrovascular accidents such as acute ischemic strokes (AIS). This retrospective cross‐sectional study aims to characterize the contribution of PAVMs to the development of AIS in the setting of thromboembolic processes. Methods The 2010 to 2019 National Inpatient Sample was queried for patients with PAVM and AIS using International Classification of Diseases, Ninth/Tenth Revision (ICD‐9; ICD‐10) codes. Baseline demographics and outcomes of interest, including complications and hospitalization metrics, were retrospectively analyzed. Results Of 7 465 187 patients treated for an AIS, 1 864 (0.02%) were found to have a concomitant PAVM. Multivariate regression found patients with AIS‐PAVM were more likely to be aged <65 years and less likely to have traditional stroke risk factors such as cardiovascular disease, obesity, or smoking. Furthermore, in propensity‐matched analysis, patients with AIS‐PAVM were more likely to experience thrombosis‐related pathologies and vascular complications. Patients with AIS‐PAVM were also more likely to receive a mechanical thrombectomy or intravenous thrombolysis, yet the mortality between those with PAVMs and those without did not differ significantly. Still, patients with AIS‐PAVM incurred significantly prolonged stays in the hospital and increased total charges. Conclusion Given the relative rarity of PAVMs, a high index of suspicion, especially in the setting of deep vein thrombosis, is necessary to identify this condition in a timely manner when evaluating cryptogenic AIS. Abnormal right‐to‐left shunting through pulmonary vasculature may serve as a conduit for the translation of a deep vein thrombosis paradoxically into a distal occlusion of cerebral arteries. Our findings substantiate that AIS may follow a vastly different disease process in patients with PAVM.